The Effect of Awareness, Trust and Brand Image on Intention to Use Sharia Insurance Products with Knowledge as a Moderating Variable in Medan Belawan - Indah Ussania; Isnaini Harahap; Juliana Nasution (Dinasti Publisher, 2024)
The purpose of this study was to determine the effect of awareness, trust and brand image on the intention to use Islamic insurance products with knowledge as a moderating variable in Medan Belawan. The population in this study were Islamic insurance customers in Medan Belawan. The sampling technique used purposive sampling with a total of 100 respondents. The data analysis technique applied in this research is quantitative analysis by applying Moderated Regression Analysis (MRA). The results showed that: (1) awareness has a significant influence on increasing the intention of Sharia insurance products in Medan Belawan. The value of t count> t table or -2.600 < 1.660881 and obtained a significance value < 0.05 alpha level or 0.011 < 0.05. (2) trust has a significant influence on increasing the intention of respondents of Sharia insurance products in Medan Belawan. The value of the t value> t table or 2, 329> 1.660881 and obtained a significance value < alpha level 0.05 or 0.022 < 0.05. Thus, the hypothesis can be accepted. (3) brand image has a significant influence on increasing the intention of Sharia insurance products in Medan Belawan. The value of t value> t table or or 2, 766> 1.660881 and obtained a significance value < alpha level 0.05 or 0.007 < 0.05, so the hypothesis is accepted. (4) knowledge is able to moderate the influence of awareness, trust, and brand image variables on the intention of Sharia insurance products in Medan Belawan.